Exploring the independent prescribing role of the community pharmacists in Wales. (26th March 2021) - Alghamdi, S S; Deslandes, R; White, S; Hodson, K; Mackridge, A; Isaac, K; Maolod, N; Hyde, E
Abstract: Introduction: Since 2019, the role of independent pharmacist prescribers (IPPs) in primary care has extended to community pharmacies in Wales [1]. This was in response to a Welsh Pharmaceutical Committee report in 2019 that outlined a plan to include an IPP in each community pharmacy in Wales by 2030. This aimed to relieve pressure on general practices, enhance patient care and reduce referral and admission rates to secondary care [2]. As funding was provided by the Government, the number of community pharmacists completing the independent prescribing course increased and many have implemented their prescribing role. Aim: To explore the views of community IPPs regarding their prescribing role within community pharmacies in Wales. Methods: Semi-structured face-to-face and telephone interviews were conducted with community IPPs from all seven health boards (HBs) in Wales. Ethical approval was obtained from the School of Pharmacy and Pharmaceutical Sciences at Cardiff University and the School of Pharmacy and Bioengineering at Keele University. Purposive sampling was used to identify potential participants. Gatekeepers (HB community pharmacy leads and directors of IPP courses in Wales) sent invitation emails, participant information sheet and consent form to potential participants. Written consent was obtained. Interviews were audio-recorded and transcribed ad verbatim. Thematic analysis was used to analyse the data. Results: Thirteen community IPPs across Wales participated. Six themes were identified, including the utilisation of their role as community IPPs, their experiences with their independent prescribing training, motivation to obtain their prescribing qualification and utilise it, the impact, barriers and facilitators to implement and utilise their role. Participants practised as IPPs in the management of minor ailments and some other conditions, such as respiratory and sexual health. The course and training for community IPPs was helpful, but there was a need to focus more on therapeutic and clinical examination skills. The main impact of the role was that it helped to improve communication between community pharmacies and general practices and relieved some pressure on general practices. The main barriers were the lack of appropriate funding by the Government to develop the role, lack of access to patients' medical records, lack of support and high workload. "One of the areas identified as high risk is for pharmacy prescribers is the lack of access to clinical records. How can you [as community IPPs] make any sensible decisions with half the information?" IPP6 Facilitators included that some services were already in place and the drive from the 2030 vision. Conclusion: This is the first study that explored the views of community IPPs regarding their prescribing role in community pharmacies in Wales. It provided an insight into this new role that can be considered by the Welsh Government to achieve the 2030 vision for this role. A limitation to this study was that the role is still new in community pharmacies, which may affect the views of the community IPPs. Many of them have obtained their prescribing qualification but have not started to utilise it yet. Further work is needed to explore a wider population of community IPPs' experiences as the role develops. References: 1. Wickware, C. 2019. All community pharmacies in Wales to have an independent prescriber as part of long-term plan for Welsh pharmacy. Available at: https://www.pharmaceutical-journal.com/news-and-analysis/news/all-community-pharmacies . 2. Welsh Pharmaceutical Committee. 2019. Pharmacy: Delivering a Healthier Wales. Available at: https://www.rpharms.com/Portals/0/RPS%2 .